Estimation of Chemokine CCL7 Serum Level among Patients with Type 2 Diabetes Mellitus - Kawther Basim Bader Al-Noor; Abeer Thaher Naji Al-Hasnawi; Hassan Murtadha (Karbala Journal of Medicine, 2025)
Background: Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder with multiple causes that affects adults all over the world. Chemokine ligand (CC motif) 7 (CCL7) is a chemoattractant that attracts immune cells, especially macrophages and monocytes. It is thought to play a role in anti-inflammatory responses and has been associated with several diseases. The study aimed to measure chemokine CCL7 levels in the serum of T2DM patients and compare them with healthy individuals. Also, evaluate the potential diagnostic role of CCL7 as a prognostic biomarker in T2DM patients. Methods: This is a case-control study that included 100 participants, 50 participants with type 2 diabetes and 50 healthy participants as a control group. Serum was separated from blood samples, and a CCL7-specific ELISA kit was used to calculate its serum level. Results: Several statistically significant metrics were achieved, including serum CCL7 levels, which were significantly different between patients and healthy controls (p=0.001), with an area under the curve (AUC) of 0.755, which demonstrates strong diagnostic ability. Sensitivity was 0.98, and specificity was 0.5. The cut-off value in the current study was 14.583, with a p-value of 0.000, confirming statistically significant results. Conclusions: The study revealed that the chemokine CCL7 has a good ability to differentiate T2DM patients, which may make it a potential diagnostic biomarker in the future.